2011
DOI: 10.1021/es2001997
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Fat, Oil, and Grease (FOG) Deposit Formation Mechanisms in Sewer Lines

Abstract: The presence of hardened and insoluble fats, oil, and grease (FOG) deposits in sewer lines is a major cause of line blockages leading to sanitary sewer overflows (SSOs). Despite the central role that FOG deposits play in SSOs, little is known about the mechanisms of FOG deposit formation in sanitary sewers. In this study, FOG deposits were formed under laboratory conditions from the reaction between free fatty acids and calcium chloride. The calcium and fatty acid profile analysis showed that the laboratory-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 22 publications
6
50
0
Order By: Relevance
“…Keener et al (2008) observed layering effects in larger FOG-deposits where sediment and other debris were found interspersed between the hardened soap layers and also reported that mineral deposits could be mistakenly identified as FOG. As long retention times has been reported for the necessary chemical reactions to occur and the actual deposits to form (He et al, 2011) the formation of FOG deposits will most likely occur in sewers with low flow velocities (Water Research Center, 2009). Dirksen et al (2013b) analysed plastic sewers (235 mm in diameter) with respect to sagging serving mainly residential areas in Amsterdam, Netherlands.…”
Section: Impacts From Fogmentioning
confidence: 99%
See 2 more Smart Citations
“…Keener et al (2008) observed layering effects in larger FOG-deposits where sediment and other debris were found interspersed between the hardened soap layers and also reported that mineral deposits could be mistakenly identified as FOG. As long retention times has been reported for the necessary chemical reactions to occur and the actual deposits to form (He et al, 2011) the formation of FOG deposits will most likely occur in sewers with low flow velocities (Water Research Center, 2009). Dirksen et al (2013b) analysed plastic sewers (235 mm in diameter) with respect to sagging serving mainly residential areas in Amsterdam, Netherlands.…”
Section: Impacts From Fogmentioning
confidence: 99%
“…As in particular, palmitic acid has been shown to be involved in the formation mechanisms of FOG-deposits in sewers (He et al, 2011;Williams et al, 2012), Iasmin et al (2014) recommended selective removal of this oil in pre-treatment processes prior to any discharge of FOG-rich wastewater to sewers. Collection of FOG in jars distributed to individual households has been evaluated in field studies in Europe.…”
Section: Source Separation Of Fogmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids degrade to long chain fatty acids by bacterial activities, and high concentrations of long chain fatty acids are inhibitory to anaerobic microorganisms (Tritt 1992). Lipid-rich material like food wastes from restaurants is not appropriate for municipal digesters since it can readily accumulate inside the digester walls, forming hardened deposit material and reducing the digester volume capacity (He et al 2011). BW, on the other hand, are not sufficiently lipid -or proteins-rich to cause this problem.…”
Section: Stage 5: Adding Bw To Ms [35% 36% 37% 40% 42% and 44% Bwmentioning
confidence: 99%
“…Landfill of this waste is no longer permitted in many jurisdictions (Razaviarani et al, 2013). The direct drainage into the collection system is also illegal in most municipalities, because it can accumulate on pipe walls, and potentially form hardened deposits through a chemical reaction or a physical aggregation process (He et al, 2011). It was responsible for up to 47% of the reported blockages and 50e75% of sanitary sewer overflows as it tends to solidify, reduce conveyance capacity, and eventually block flow (Wang et al, 2013;Iasmin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%